Helping Hand or Grabbing Hand? Supervisory Architecture, Financial Structure and Market View - Quintyn, Marc (International Monetary Fund, 2008)
The literature stresses the importance of financial market characteristics in determining the supervisory architectures. In the real world it is not always clear to what extent market features are taken into account. We present two complementary approaches to gain insights in the above relationship. First, an empirical test of two theories-the helping and the grabbing hand view of government-seems more consistent with the latter, presuming the market demonstrates a preference for consolidation of supervisory powers. Second, a survey among financial CEOs in Italy confirms a preference for a consolidated supervisory regime and reveals only weak consistency between the views of the policymakers and the market operators